2017
DOI: 10.2217/imt-2016-0127
|View full text |Cite
|
Sign up to set email alerts
|

Donor Origin CAR T Cells: Graft Versus Malignancy Effect Without GVHD, a Systematic Review

Abstract: CD19, CD20 chimeric antigen receptor T (CAR T) cell therapy has shown promising results for the treatment of relapsed or refractory hematological malignancies. Best results have been reported in acute lymphoblastic leukemia patients with a complete response rate above 80%. Patients who received donor-derived CAR T cells for the relapsed malignancy after stem cell transplantation (allogenic hematopoietic stem cell transplant) were identified from the published trials. A total of 72 patients from seven studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 30 publications
(12 reference statements)
1
60
1
Order By: Relevance
“…In our study, we infused the reported median numbers, and the infusion was divided across into 4 days during which escalating numbers of cells were infused in consideration of the efficacy and the possibility of GVHD and related complication, such as CRS. 9,10,24 In this condition, no CRS and GVHD could been induced. Thus, further study with more cases is needed to confirm this observation.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In our study, we infused the reported median numbers, and the infusion was divided across into 4 days during which escalating numbers of cells were infused in consideration of the efficacy and the possibility of GVHD and related complication, such as CRS. 9,10,24 In this condition, no CRS and GVHD could been induced. Thus, further study with more cases is needed to confirm this observation.…”
Section: Resultsmentioning
confidence: 81%
“…The efficiency, low toxicities and low rates of complications associated with the nontransplant background are benefits of allogeneic CAR-T cells, which can overcome some limitations of autologous CAR-T cells. [9][10][11] Allogeneic CAR-T cells have been found to exert a GVL effect and diminish GVHD in a xenograft model and in a murine acute GVHD model. 12,13 CAR-T cells as a part of RIC regimens may be an approach for treating r/r ALL in haploidentical HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study systematically analyzed GVL effect and GVHD complication for 72 patients with relapsed ALL after allo-HSCT and received donor-derived CAR-T cells [38]. In this study, only 5 of 72 patients (6.9%) developed slight GVHD without other serious side effects such as CRS and CNS toxicity.…”
Section: Car-t Cells As Conditioning Regimenmentioning
confidence: 96%
“…In our analysis, RR with autologous cells was 76% and with allogeneic cells was 57% (P < 0.05). There was a significant difference in efficacy with autologous versus allogeneic cells in our analysis; other studies have also reported side effects between donor-derived CAR-T cell versus autologous CAR-T cells [58]. In a future study, we will specifically address questions about such adverse effects.…”
Section: Discussionmentioning
confidence: 80%